The potential protective role of peripheral immunophenotypes in Alzheimer’s disease: a Mendelian randomization study - Zuo, Chun-yan; Hu, Zhengwei; Hao, Xiao-yan; Li, Meng-jie; Shi, Jing-jing; Guo, Meng-nan; Ma, Dong-rui; Li, Shuang-jie; Liang, Yuan-yuan; Zhang, Chan; Mao, Cheng-yuan; Xu, Yuming; et al. (Frontiers in Aging Neuroscience, 2024)
Introduction: Alzheimer's disease (AD) is the most widespread neurodegenerative disease in the world. Previous studies have shown that peripheral immune dysregulation plays a paramount role in AD, but whether there is a protective causal relationship between peripheral immunophenotypes and AD risk remains ambiguous. Methods: Two-sample Mendelian randomization (MR) was performed using large genome-wide association study (GWAS) genetic data to assess causal effects between peripheral immunophenotypes and AD risk. Utilizing the genetic associations of 731 immune cell traits as exposures. We adopted the inverse variance weighted method as the primary approach. The Weighted median and MR-Egger regression methods were employed as supplements. Various sensitivity analyses were performed to assess the robustness of the outcomes. Results: Based on the IVW method, we identified 14 immune cell traits that significantly reduced the risk of AD, of which six demonstrated statistical significance in both IVW and Weighted median methods. Among the seven immune traits, four were related to regulatory T (Treg) cells : (1) CD25++ CD45RA- CD4 not regulatory T cell % T cell (odds ratio (OR) [95% confidence interval (CI)] = 0.96 [0.95,0.98], adjusted P = 1.17E-02), (2) CD25++ CD45RA- CD4 not regulatory T cell % CD4+ T cell (OR [95% CI] = 0.97 [0.96,0.99], adjusted P = 3.77E-02), (3) Secreting CD4 regulatory T cell % CD4 regulatory T cell (OR [95% CI] = 0.98 [0.97,0.99], adjusted P = 7.10E-03), (4) Activated & secreting CD4 regulatory T cell % CD4 regulatory T cell(OR [95% CI] = 0.98 [0.97,0.99], adjusted P = 7.10E-03). In addition, HLA DR++ monocyte % monocyte (OR [95% CI] = 0.93 [0.89, 0.98], adjusted P = 4.87E-02) was associated with monocytes, and HLA DR on myeloid Dendritic Cell (OR [95% CI] = 0.93 [0.89, 0.97], adjusted P = 1.17E-02) was related to dendritic cells (DCs). Conclusion: These findings enhance the comprehension of the protective role of peripheral immunity in AD and provide further support for Treg and monocyte as potential targets for immunotherapy in AD.